Platelet-Rich Plasma and Platelet-Rich Fibrin Can Induce Apical Closure More Frequently Than Blood-Clot Revascularization for the Regeneration of Immature Permanent Teeth: A Meta-Analysis of Clinical Efficacy - Murray, Peter E. (Frontiers in Bioengineering and Biotechnology, 2018)
The purpose of this review was to compare the clinical efficacy of platelet-rich plasma (PRP) and platelet-rich fibrin (PRF), versus blood clot revascularization (BCR) for the regeneration of immature permanent teeth. A survey of the literature identified 174 cases of immature permanent teeth which had been given PRP, PRF or BCR regeneration treatment with a year-long follow-up in six different articles. A meta-analysis of the 174 immature permanent teeth after one year, were compared to assess the ability of PRP, PRF and BCR to accomplish apical closure, a periapical lesion healing response, root lengthening, and dentinal wall thickening. The mean success rate for apical closure after one year was: PRP (89.2%) PRF (80%), and BCR (57.1%). The mean success rate for root lengthening after one year was: BCR (88.9%), PRP (68.2%), and PRF (65%). The periapical lesion healing response was 88.9% for BCR and 100% for PRP. Dentinal wall thickening was 100% for BCR, and 100% for PRP. Apical closure occurred more frequently following PRP and PRF than with BCR (Fischer test, P < 0.0029), for all the other effects the PRP, PRF, and BCR treatments were similarly effective (Fischer test, P > 0.05). In conclusion, the fractured or decayed immature permanent teeth of children and young adults aged 6 years to 28 which have a restorable crown, but thin dentinal walls may be regenerated by using a revascularization procedure which draws blood and stem cells into a disinfected root canal space. Although BCR is most common revascularization method, apical closure may occur more frequently if PRF and PRP are used instead of BCR for the regeneration of immature permanent teeth. The proper use of regenerative procedures can be very successful at the disinfection of bacteria from the periapical region of immature permanent teeth, which helps to heal loalized lesions, and avoid the need for complex apical surgery, in addition to regenerating tissues to strengthen the structure of immature teeth, to help prevent tooth fracture and tooth loss.